Electro-catalytic material, preparation method thereof and method for electro-catalytically synthesizing acetamido aromatic compound

The development of transition metal-based electrocatalytic materials enables the efficient, environmentally friendly, and cost-effective synthesis of ethylamine aromatic compounds by electrochemically reducing nitroaromatics at room temperature and atmospheric pressure, addressing the limitations of existing methods and offering a scalable industrial solution.

CN119615270APending Publication Date: 2025-03-14JIANGNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411818758.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Current methods for producing ethylamine aromatic compounds, such as acetaminophen, face environmental and operational challenges, including high energy requirements, equipment corrosion, and low economic efficiency, limiting their industrial application. Additionally, existing electrocatalytic methods face inefficiencies in multi-electron coupled proton transfer processes and low ring efficiency.

Method used

A method involving the preparation of transition metal-based electrocatalytic materials through a process that includes loading a conductive substrate with transition metal salts and organic ligands, followed by a water-heating reaction to form MOFs, which are then used in an electrochemical system to catalytically reduce nitroaromatic compounds to ethylamine aromatic compounds at room temperature and atmospheric pressure.

Benefits of technology

This approach results in a green, pollution-free, and cost-effective synthesis of ethylamine aromatic compounds, with improved catalytic activity and scalability, suitable for industrial applications, utilizing water as a hydrogen source and enabling efficient conversion of nitroaromatics to high-value chemicals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615270A_ABST
    Figure CN119615270A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis, and particularly relates to a method for synthesizing an acetamido aromatic compound through electro-reduction of nitryl and application of the acetamido aromatic compound. According to the invention, a transition metal electro-catalytic material is firstly prepared, and the material is used as a cathode material for preparing the acetamido aromatic compound through electro-catalytic reduction. The preparation method comprises the following steps: putting a nitro compound, an anhydride compound and an electrolyte into an aqueous solution, reducing the aromatic nitro compound at a cathode, and coupling acetylation reaction to prepare the acetamido aromatic compound. The method comprises the following steps: by taking water as a hydrogen source, reducing a nitro compound through an electro-catalytic hydrogenation reaction, and combining with an acetylation reaction to obtain an acetamido aromatic compound; the method has the advantages of high reaction chemical selectivity, high yield, strong universality, simple operation, mild reaction conditions, low energy consumption and easy product separation. Meanwhile, the electrocatalyst material is simple to prepare, low in cost, recyclable and capable of being prepared on a large scale, and has a wide industrial application prospect in the fields of industrial electrocatalytic organic synthesis and new energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysts, and specifically relates to a method and application of synthesizing acetylamino aromatic compounds by electroreduction of nitro groups. Background Art

[0002] Nitroaromatic compounds are a class of highly toxic, highly carcinogenic and poorly biodegradable organic compounds. They are widely present in industrial and agricultural production processes and are an important class of chemical raw materials and synthetic intermediates. They are widely used in production and life. For example, they can be used as intermediates for explosives, spices and dyes, and are also important functional groups in many medicines and pesticides.

[0003] Acetamino aromatic compounds play an important role in production and life, and are widely used in fertilizers, textiles, pharmaceuticals, plastics and other fields, and are an important industrial raw material. For example, acetaminophen or acetyl-paraaminophenol (APAP), also known as paracetamol, is one of the most widely used over-the-counter (OTC) active pharmaceutical ingredients in the world.

[0004] The production of acetamino aromatic compounds represented by paracetamol in the prior art has serious environmental unfriendly problems, including the generation of a large amount of waste acid, high equipment corrosion, harsh reaction conditions, poor atom economy and other disadvantages, and its development is restricted. The Chinese invention patent with publication number CN113754554A discloses a one-step hydrogenation synthesis method for paracetamol. The method uses a hydrogenation metal catalyst, adds p-nitrophenol and acetate to an autoclave, fills with hydrogen, and catalytically hydrogenates and amidates at a specific reaction temperature to obtain the product paracetamol. However, the synthesis conditions of this method require a high temperature of 120 to 180°C and fills with 5 to 20 atmospheres of hydrogen, resulting in high cost and production difficulty of the method, low safety, and limiting the application of the process. Electrocatalytic synthesis technology can convert toxic nitroaromatic compounds into acetamino aromatic compounds through simple processes, green and mild conditions, and water as a hydrogen source through electrocatalyst hydrogenation. However, electrocatalytic synthesis also has some challenges. In particular, the multi-electron coupled proton transfer process involves thermodynamically and kinetically unfavorable processes, poor ring efficiency, etc. Exploring new electrocatalysts for the synthesis of acetyl aromatics such as acetaminophen is crucial for the widespread commercialization of the above-mentioned new and green energy systems.

[0005] Therefore, it is necessary to develop a method for synthesizing acetylamino aromatic compounds with a short synthetic route, green and pollution-free, at room temperature and pressure. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the first object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a transition metal-based electrode material:

[0009] When the transition metal electrocatalytic material comprises a transition metal element; the preparation method comprises steps S11 and S12:

[0010] S11. Immersing the conductive substrate in a system of transition metal salt and organic ligand for loading;

[0011] S12. The conductive substrate loaded in step S11 is transferred to a reactor for a hydrothermal reaction. After the reaction is completed, the substrate is washed and dried to obtain a transition metal electrocatalytic material.

[0012] or,

[0013] When the transition metal electrocatalytic material comprises at least two transition metals, the preparation method comprises steps S21, S22, and S23;

[0014] S21. The first transition metal salt is heated to a molten salt state and then loaded on a conductive substrate;

[0015] S22. placing the substrate loaded in step S21 in an aqueous solution containing an organic ligand to react and obtain a transition metal MOFs precursor material;

[0016] S23. placing the precursor material obtained in step S22 in an alkaline aqueous solution containing a second transition metal to perform a hydrothermal reaction, and after completion, washing and drying, a transition metal electrocatalytic material can be obtained on the substrate;

[0017] The transition metal is selected from one or a combination of iron, cobalt, nickel and copper;

[0018] The substrate comprising the transition metal electrocatalytic material is a transition metal electrocatalytic material electrode.

[0019] In some embodiments of the present invention, the conductive substrate electrode is immersed in a transition metal molten salt solution, and after a period of reaction, a substrate loaded with transition metal salt is obtained, and the substrate solution is ultrasonically treated in water and anhydrous ethanol in turn, and finally the loaded transition metal salt substrate is placed in a vacuum drying oven for drying. The above-mentioned loaded transition metal salt substrate is transferred to an aqueous solution of an organic ligand, stirred evenly, and the reaction is completed at room temperature, washed with anhydrous ethanol and deionized water, and the sample is vacuum dried to obtain the prepared transition metal MOFs precursor, and the precursor is placed in an alkaline aqueous solution containing a second metal for hydrothermal reaction, and finally the obtained electrode material is washed with anhydrous ethanol and deionized water, and the sample is vacuum dried to obtain an electrode material for electrocatalytic reduction reaction.

[0020] In one embodiment of the present invention, the preparation method of the transition metal heterojunction material electrode material includes: heating the copper source to a molten salt state and then loading it on a conductive substrate, further reacting with an aqueous solution containing an organic ligand to obtain a transition metal MOFs precursor material, placing it in an alkaline aqueous solution of a cobalt source to perform a hydrothermal reaction, and washing and drying after the reaction.

[0021] In one embodiment of the present invention, the preparation method of the transition metal heterojunction material electrode material includes: heating the cobalt source to a molten salt state and then loading it on a conductive substrate, further reacting with an aqueous solution containing an organic ligand to obtain a transition metal MOFs precursor material, placing it in an alkaline aqueous solution of a copper source to perform a hydrothermal reaction, and washing and drying after the reaction.

[0022] In step S21, the conductive substrate is selected from one or more of carbon paper, nickel foam, copper foam, and stainless steel mesh.

[0023] Furthermore, in step S21, the first transition metal salt is an ionic liquid or a low-temperature molten salt; the melting point of the low-temperature molten salt is lower than 400°C;

[0024] Furthermore, the ionic liquid is a molten salt that is in a liquid state at a temperature below 100° C., including but not limited to one or more of imidazoles, ammonium salts, and tetrafluoroborate salts of the first transition metal;

[0025] In some embodiments of the present invention, in step S21, the conductive substrate is immersed in the first transition metal salt for a time of ≥5 min;

[0026] Furthermore, the conductive substrate is selected from one or more of carbon paper, nickel foam, copper foam, and stainless steel mesh.

[0027] Preferably, the conductive substrate size is 0.1 cm 2 Above; In one embodiment, a nickel foam substrate is used, the size of which is 4 cm×4 cm;

[0028] Further, the organic ligand is at least one of 2,5-dihydroxyterephthalic acid, terephthalic acid, syringic acid, gallic acid, and 1,3,5-tricarboxylic acid;

[0029] In some embodiments of the present invention, the molar ratio of the transition metal to the organic ligand is 1:0.1 to 1:10.

[0030] In some embodiments of the present invention, the hydrothermal reaction step is adjusted to a pH of 7-9 by sodium hydroxide, ammonia, urea, or thiourea;

[0031] In some embodiments of the present invention, the hydrothermal reaction temperature is 120-200° C., and the hydrothermal reaction time is ≥30 min.

[0032] In some preferred embodiments, the first transition metal is a cobalt source solution, which is any one of a cobalt salt aqueous solution, a cobalt salt ionic liquid, and a cobalt salt low-temperature molten salt, wherein the low-temperature molten salt includes at least one of a cobalt salt or an ionic liquid having a melting point below 400°C; the ionic liquid includes a molten salt that is in a liquid state at a temperature below 100°C, one or more of imidazoles, ammonium salts, and tetrafluoroborates; the second transition metal is copper, including at least one of copper nitrates, chlorides, sulfates, phosphates, acetates, and carbonates, wherein the molar ratio of Co to Cu is 1:0.1 to 5.

[0033] In some preferred embodiments, the size of the nickel foam substrate is at least 4 cm×4 cm, and it is immersed in a cobalt source solution, wherein the insulation temperature is 90-120° C., the time is 6-10 h, the ultrasonic time is 10 min, and the vacuum drying temperature is 60° C., and the time is 5-6 h.

[0034] As a preferred embodiment of the preparation method of the present invention, the stirring time of the above-mentioned base solution loaded with cobalt molten salt being transferred into the 2,5-dihydroxyterephthalic acid solution is 30 minutes, the reaction temperature is 120-160° C., and the reaction time is 5-10 hours.

[0035] The precursor of the cobalt-based MOFs is transferred into a copper nitrate and urea aqueous solution at a reaction temperature of 140° C. for 8 to 12 hours.

[0036] As a preferred embodiment of the preparation method of the present invention, the washing times with anhydrous ethanol and deionized water are greater than 3 times, and the sample after washing is vacuum dried at a temperature of 60° C. for 6 hours.

[0037] As a preferred embodiment of the preparation method of the present invention, the Co-Cu electrode material has a molar ratio of Co and Cu of about 0.5:1, and the volume of the formed solution is 10 to 100 mL.

[0038] The second aspect of the present invention is to provide a transition metal heterojunction electrocatalytic material prepared by the preparation method described above.

[0039] In some embodiments, the transition metal heterojunction electrocatalytic material is a Co-Cu heterojunction material, wherein the molar ratio of Co to Cu is 1:0.1-5;

[0040] Furthermore, the transition metal heterojunction electrocatalyst is used in the fields of electrocatalytic treatment of wastewater containing nitrate salts, soil treatment, coatings, anti-counterfeiting, printing, textiles, toxic gas adsorption environmental engineering, synthesis of pharmaceutical intermediates, and electrocatalytic reduction of organic nitrobenzene and its derivatives to amines. The electrode material is used as a cathode catalyst to electrocatalytically reduce nitrobenzene and its derivatives to reduce coupled anhydrides to amide-type high-value-added chemicals.

[0041] In some embodiments of the present invention, the transition metal heterojunction electrocatalytic material is a Co-Cu heterojunction material, and a sheet-like or columnar component is grown on a MOF substrate to form a heterojunction with a length of micrometers.

[0042] The third aspect of the present invention is to provide a method for electrochemically synthesizing acetylamino aromatic compounds based on the transition metal heterojunction electrocatalyst prepared by the present invention.

[0043] A method for electrochemically synthesizing acetylamino aromatic compounds, comprising: using an aromatic nitro compound, an acid anhydride compound, and an aqueous electrolyte solution, and using a transition metal heterojunction material electrode as a working electrode to construct an electrochemical reduction system, and reducing the aromatic nitro compound at a cathode to prepare the acetylamino aromatic compound;

[0044] In some embodiments, the aromatic nitro compound is selected from nitrophenol, nitrobenzoic acid, and nitrobenzene.

[0045] In some embodiments, the acid anhydride compound is at least one of acetic anhydride, glyoxylic acid, and pyruvic anhydride;

[0046] Further, the electrochemical reduction system is a three-electrode system, further comprising a reference electrode and a counter electrode;

[0047] Furthermore, the electrolyte solution is a neutral buffered aqueous solution, so that the pH value during the reaction is controlled at 6-8.

[0048] Further, the electrolyte is selected from sodium (hydrogen) phosphate, potassium (hydrogen) phosphate, sodium sulfate, potassium sulfate or sodium chloride, potassium chloride, potassium (hydrogen) carbonate, sodium (hydrogen) carbonate;

[0049] Further, the electrolyte concentration is 0.01-0.1M;

[0050] Furthermore, the electrolysis voltage is -0.2V to -0.8V, and the constant voltage reaction is ≥30min.

[0051] Further, the concentration range of the aromatic nitro compound is 10-100 mM;

[0052] The counter electrode is selected from a graphite electrode and a platinum electrode;

[0053] The reference electrode is a calomel electrode;

[0054] Furthermore, the preparation method can be applied to the preparation of acetaminophen and acetyl-p-aminophenol.

[0055] As a preferred embodiment of the preparation method of the present invention, the Co-Cu electrode material is used as a working electrode in an electrolytic cell, and the electrolyte is a mixed solution containing p-nitrobenzoic acid and acetic anhydride, with a concentration of more than 10 mM, and the ratio of acetic anhydride to water is 1:4.

[0056] As a preferred embodiment of the preparation method of the present invention, the application system is a three-electrode system, an H-type electrolytic cell is used, a stone mill rod sheet / platinum sheet is used as the counter electrode, a reference electrode is a calomel electrode, the electrolyte solution is a neutral potassium phosphate solution, the pH is about 7, the electrolysis voltage is 0.4V to -0.8V, and the constant voltage reaction is for more than 0.5h.

[0057] As a preferred embodiment of the preparation method of the present invention, the Co-Cu electrode material is used as a cathode catalyst, and p-nitrophenol and acetic anhydride can be converted into high-value-added chemicals such as sodium salt, potassium salt and ammonium salt corresponding to p-acetaminophenol through electrocatalytic reduction.

[0058] As a preferred embodiment of the preparation method of the present invention, the application of the electrode material in electrocatalytic synthesis can realize the large-scale synthesis of high-value-added chemicals by continuously adding raw materials p-nitrophenol and acetic anhydride during the reaction process, thereby realizing the electrosynthesis of gram-level p-acetaminophenol.

[0059] Compared with the prior art, the present invention has at least the following beneficial effects:

[0060] (1) The present invention first provides a method for preparing an electrode material, which uses a simple synthesized transition metal molten salt to synthesize a MOFs precursor at room temperature, and then forms an integrated electrode material through low-temperature hydrothermal treatment, thereby optimizing the surface morphology and improving the catalytic activity of the material. The material preparation process is simple, can be synthesized in batches, has low raw material costs, and meets the requirements of industrial applications.

[0061] (2) The present invention provides a method for electrochemically synthesizing acetylamino aromatic compounds based on the above-mentioned electrode materials; a nitro compound, an acid anhydride compound, an electrocatalyst and an electrolyte are placed in an aqueous solution, the aromatic nitro compound is reduced at the cathode and coupled to an acetylation reaction to prepare an acetylamino aromatic compound.

[0062] (3) The present invention uses only green energy, water as a hydrogen source, and abundant transition metals as electrocatalysts. Through electrocatalytic hydrogenation, the reduction of nitro compounds is achieved and acetylation reaction is combined to obtain acetylamino aromatic compounds with high attachment values. The synthesis method has the characteristics of green environmental protection, simple operation, high chemical selectivity, high yield, and strong universality. In addition, the process is simple to operate, the reaction conditions are mild, the energy consumption is low, the product is easy to separate, and the electrocatalyst material is simple to prepare, low in cost, recyclable, and can be prepared on a large scale; it has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0064] Among them: The electrode material is referred to as CM-74 / Cu(OH) 2 .

[0065] Figure 1 The typical CM-74 / Cu(OH) 2 Powder X-ray diffraction patterns of electrode materials and precursor CNH-MOF-74;

[0066] Figure 2 The typical CM-74 / Cu(OH) 2 SEM images of electrode materials;

[0067] Figure 3 CM-74 / Cu(OH) 2 XPS spectrum of electrode materials;

[0068] Figure 4 CM-74 / Cu(OH) 2 The electrode material is 5mVs -1 The polarization curve of the scanning rate;

[0069] Figure 5 CM-74 / Cu(OH) 2 Liquid chromatogram of the product obtained from the electrode material;

[0070] Figure 6 CM-74 / Cu(OH) 2 Yield plots of cycling stability of electrode materials;

[0071] Figure 7 Electrode materials prepared in Example 1 and Example 2 (a Example 2, b Example 1);

[0072] Figure 8 Polarization curves of the electrode materials prepared in Example 1 and Example 2. DETAILED DESCRIPTION

[0073] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0074] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0075] The electrochemical reactions in the examples were carried out using Shanghai Chenhua 760E electrochemical workstation;

[0076] Performance characterization method:

[0077] Calculation of synthesis yield: The yield of the electrocatalytic reaction was calculated from the liquid chromatography data: the relative yield of the product was calculated using the ratio of the peak area of ​​a single product to the total peak area.

[0078] In the examples, a variety of catalysts were prepared and the effects of electrocatalytic preparation of acetamino aromatic compounds were verified respectively; the raw materials used included nitrophenol, nitrobenzoic acid, and nitrobenzene, and acetaminophenol, acetaminobenzoic acid, and acetaminobenzene were prepared respectively, and the yield and selectivity were measured by liquid chromatography.

[0079] Example 1 A large-scale preparation method of Co-Cu based heterojunction materials:

[0080] (1) 10 g of cobalt nitrate was placed in a polytetrafluoroethylene inner chamber containing 100 mL, and then placed in an oven and kept at 120°C for 6 h. A 4*4 cm flat piece of nickel foam was placed in the oven and immersed in the cobalt nitrate solution to obtain basic cobalt nitrate (denoted as CNH) grown in situ on the nickel foam.

[0081] (2) CNH was ultrasonically treated in water and anhydrous ethanol for 10 min, and finally CNH was placed in a vacuum drying oven at 60°C for 6 h; 2 g of 2,5-dihydroxyterephthalic acid was dissolved in acetonitrile, stirred evenly, and then CNH was transferred to the solution, kept at 120°C for 8 h, washed with anhydrous ethanol and deionized water for more than 3 times, and placed in a vacuum drying oven at 60°C for 6 h to obtain MOF generated by basic cobalt nitrate (referred to as CNH-MOF-74).

[0082] (3) 2 g of copper nitrate was put into a 100 mL beaker and stirred, and the aluminum nitrate solution and CNH-MOF-74 were put into a reactor and kept at 140°C for 6 h; the mixture was naturally cooled to room temperature, and washed with anhydrous ethanol and deionized water for more than 3 times. The prepared sample was vacuum dried at 60°C for 6 h to obtain the prepared electrode material (CM-74 / Cu(OH) 2 ).

[0083] The steps for electrochemical synthesis of paracetamol are as follows:

[0084] A platinum anode and cathode material and a calomel reference electrode were respectively inserted into an H-type electrolytic cell, and p-nitrophenol (1 mmol) was added in sequence, followed by a neutral potassium phosphate solution (40 mL), and then acetic anhydride (10 mL); electrolysis was performed at room temperature at a potential of -0.545 V vs. RHE for 8 h; at the end of the reaction, a large amount of precipitation was generated in the system, and the liquid was firstly filtered out with a high performance liquid chromatography to obtain a concentration of 1, and then water was added to the system to wash 3 times, and then centrifuged and dried, and the precipitate was collected, dissolved with a neutral phosphate solution, and filtered out with a high performance liquid chromatography to obtain a concentration of 2, and the two concentrations were added to obtain the product paracetamol yield.

[0085] The steps for electrochemical synthesis of acetaminobenzoic acid are as follows:

[0086] A platinum anode and cathode material and a calomel reference electrode were respectively inserted into an H-type electrolytic cell, and p-nitrobenzoic acid (1 mmol) was added in sequence, followed by a neutral potassium phosphate solution (40 mL), and then acetic anhydride (10 mL); electrolysis was performed at room temperature at a potential of -0.545 V vs. RHE for 5 h; at the end of the reaction, a large amount of precipitation was generated in the system, and the liquid was first filtered out with a high performance liquid chromatography to obtain a concentration of 1, and then water was added to the system to wash 3 times, and then centrifuged and dried, the precipitate was collected, dissolved with a neutral phosphate solution, and filtered out with a high performance liquid chromatography to obtain a concentration of 2, and the two concentrations were added to obtain the yield of the product p-acetaminobenzoic acid.

[0087] The steps for electrochemical synthesis of 4-acetaminophen are as follows:

[0088] A platinum anode and cathode material and a calomel reference electrode were respectively inserted into an H-type electrolytic cell, and p-nitrobenzene (0.5 mmol) was added in sequence, and then added to a neutral potassium phosphate solution (40 mL), and then acetic anhydride (10 mL) was added; electrolysis was carried out at room temperature at a potential of -0.545 V vs. RHE for 4 hours; at the end of the reaction, a large amount of precipitation was generated in the system, and the liquid was first filtered out with a high performance liquid chromatography to obtain a concentration of 1, and then water was added to the system to wash 3 times, and then centrifuged and dried, the precipitate was collected, dissolved with a neutral phosphate solution, and filtered out with a high performance liquid chromatography to obtain a concentration of 2, and the two concentrations were added to obtain the yield of the product p-acetaminobenzene.

[0089] Use the prepared (CM-74 / Cu(OH) 2 ) electrode material is used as cathode to electrocatalyze the preparation of acetylamino aromatic compounds; the yield of paracetamol is 38%, acetylaminobenzoic acid is 62%, and acetylaminobenzene is 51%.

[0090] Example 2

[0091] (1) 10 g of cobalt nitrate was placed in a polytetrafluoroethylene inner tube containing 100 mL, and a 4*4 cm flat piece of nickel foam was placed in a beaker to immerse it in the cobalt nitrate solution and kept at 120°C for 6 h. The mixture was then placed in a reactor and then in an oven. CNH was ultrasonically treated in water and anhydrous ethanol for 10 min. Finally, the CNH was placed in a vacuum drying oven at 60°C for 6 h to obtain basic cobalt nitrate (referred to as CNH) grown in situ on the nickel foam.

[0092] (2) Dissolve 2 g of tricarboxybenzene in water and stir evenly. Then transfer CNH into the solution and keep it at room temperature for 5 h. Take it out and wash it with anhydrous ethanol and deionized water for more than 3 times. Put it in a vacuum drying oven and dry it at 60 ° C for 6 h to obtain Co(H3btc) generated by basic cobalt nitrate.

[0093] (3) 2 g of copper nitrate was put into a 100 mL beaker and stirred, and the copper nitrate solution and Co(H3btc) were put into a reactor together and kept at 120°C for 8 h; the mixture was naturally cooled to room temperature, and washed with anhydrous ethanol and deionized water for more than 3 times. The prepared sample was vacuum dried at 60°C for 6 h to obtain the prepared electrode material (Co(H3btc) / Cu(OH) 2 ).

[0094] Co(H3btc) / Cu(OH) 2 The method and steps of electrocatalytic synthesis are the same as those of Example 1, except that the cathode material is different.

[0095] When this material is used as a cathode for electrochemical synthesis, the yield of paracetamol is 35%, acetaminobenzoic acid is 59%, and acetaminobenzene is 44%.

[0096] Example 3

[0097] Preparation of catalytic materials: Place 1g of cobalt nitrate and 1g of syringic acid in a 100mL polytetrafluoroethylene inner chamber, and take a 4*4cm flat piece of nickel foam and place it in a beaker to immerse it in the solution (the solvent is DMF), then put it into a reactor, and then place it in an oven and keep it at 140℃ for 10h, ultrasonically treat it in water and anhydrous ethanol for 10min, and finally put it in a vacuum drying oven at 60℃ for 6h to obtain the in-situ growth material on the nickel foam.

[0098] When this material is used as a cathode for electrocatalytic synthesis of acetylamino aromatic compounds, the yield of paracetamol is 23%, p-acetylaminobenzoic acid is 55%, and p-acetylaminobenzene is 40%.

[0099] Example 4

[0100] Preparation of catalytic materials: 1g of cobalt nitrate and copper nitrate and 3g of 2,5-dihydroxyterephthalic acid are placed in a 100mL polytetrafluoroethylene inner village, then put into a reactor, and then placed in an oven, and a 4*4cm flat piece of nickel foam is placed in a beaker to immerse it in the solution, and kept warm at 120℃ for 6h, ultrasonically treated in water and anhydrous ethanol for 10min, and finally placed in a vacuum drying oven at 60℃ for 6h to obtain an in-situ growth material on the nickel foam.

[0101] When this material is used as a cathode for electrocatalytic synthesis of acetylamino aromatic compounds, the yield of paracetamol is 20%, 45% of acetylaminobenzoic acid, and 41% of acetylaminobenzene.

[0102] Example 5

[0103] Preparation of catalytic materials: 1g of copper nitrate and 1g of syringic acid were placed in a 100mL polytetrafluoroethylene inner chamber, and a 4*4cm flat piece of nickel foam was placed in a beaker to immerse it in the solution, and then placed in a reactor, and then placed in an oven and kept warm at 140°C for 10h, ultrasonically treated in water and anhydrous ethanol for 10min, and finally placed in a vacuum drying oven at 60°C for 6h to obtain an in-situ grown material on the nickel foam, and then in-situ reduced for 600s at a potential of 1.2V vs.RHE to obtain SyA-Cu / CuO.

[0104] When this material is used as a cathode for electrocatalytic synthesis of acetylamino aromatic compounds, the yield of paracetamol is 22%, p-acetylaminobenzoic acid is 61%, and p-acetylaminobenzene is 41%.

[0105] Example 6

[0106] Take Example 1 to synthesize 4*4cm 2 Size of CM-74 / Cu(OH)2 Electrode; put in 25mmol 4-NP reaction raw material (about 3.5g), with a diameter of 4*4cm 2 Size of CM-74 / Cu(OH) 2 As an electrode, after 50 hours of reaction, the reaction solution was diluted and analyzed by high performance liquid chromatography, and the yield was 39.5%, indicating that the electrode material has the advantage of being scalable under electrosynthesis conditions. The crystal structure of the Co-Cu based heterojunction material prepared in Example 1 was analyzed:

[0107] Powder X-ray diffraction was carried out on a D8 X-ray powder diffractometer from Bruker, Germany, with a fixed target monochromatic light source of Cu-Kα and a wavelength of The scanning range is 5-60° and the scanning step is 0.02°. Sample 1# is a typical electrode material prepared in Example 1.

[0108] like Figure 1 The X-ray diffraction pattern obtained by fitting is Figure 1 By comparing the spectra obtained by X-ray diffraction test after scraping the powder from sample 1#, it can be found that the prepared heterojunction contains Co-MOF-74 and Cu(OH) 2 (PDF#42-0638) shows that under mild and environmentally friendly conditions, basic cobalt nitrate can be easily grown on nickel foam in the form of molten salt on a large scale, and then the ligand and copper source are introduced by a mild solvothermal method to smoothly form a regular Co-Cu based heterojunction electrode material on the substrate.

[0109] like Figure 2 As shown on the left, the Co-Cu based heterojunction material prepared in Example 1 was subjected to characterization tests. The prepared precursor material as a whole presents a regularly stacked spherical structure with a length of micrometers and a relatively uniform morphology, which is smaller in size than the existing materials. Figure 2 As shown on the right, after the copper source is introduced, a large number of nanoparticles grow and cover the original surface to form a heterojunction structure, which increases the contact area between the catalyst and the reaction substrate and exposes more reaction active sites, thereby improving the catalytic activity of the catalyst.

[0110] Figure 3 The XPS spectra of the Co-Cu based heterojunction electrode material and the precursor CNH-MOF-74 described in Example 1 confirm the presence of Co, Cu, O and C on the surface of the electrocatalyst by X-ray photoelectron spectroscopy (XPS), which is consistent with the results of EDS, and further study the chemical composition and chemical state of the surface of these products. It can be seen from the Cu graph that there are two peaks with binding energies of 932.6eV and 934.5eV, indicating the presence of Cu 2+ and Cu +In the Co spectrum, two groups of peaks can be seen, namely the peaks with binding energies of 779.3 eV and 781.1 eV, indicating the presence of Co 2+ and Co 3+ In the O spectrum, three main peaks can be clearly identified: Metal-O bond (530.7 eV), Metal-OH bond (531.5 eV), and surface adsorbed water molecules (533.0 eV).

[0111] The CM-74 / Cu(OH) prepared in Example 1 2 The heterojunction electrode material was used as the working electrode, and the calomel electrode and Pt sheet were used as the reference electrode and counter electrode, respectively. 0.1 M PBS neutral solution and 10 mM p-nitrophenol (4-NP) were used as the electrolyte and electrolyte, respectively. The electrochemical workstation was operated at 5 mV·s -1 The LSV polarization curve test was performed at a rate of 100 mV / s. Before the linear sweep voltammetry (LSV) test, 20 cycles were scanned at 100 mV / s to reach a stable state, and then the test was performed at a scan rate of 5 mV / s. The potential value was calculated according to the equation E vs RHE = E vs SCE + 0.2412 + 0.0591 pH, where E vs RHE is the relative reversible hydrogen electrode potential (V) and E vs SCE is the relative saturated calomel electrode potential (V). The polarization curve is shown in Figure 4 As shown in the figure, CM-74 / Cu(OH) 2 The heterojunction electrode material has excellent performance for the reductive coupling of 4-NP with acetic anhydride, meets the industrial current density requirements, and can be used in industrial production applications.

[0112] CM-74 / Cu(OH) prepared in Example 1 2 Electrocatalysis of 0.1 M PBS neutral solution containing 10 mM 4-NP was performed, and the obtained product was characterized by liquid chromatography, as shown in FIG. Figure 5 As shown, it is the retention time and peak area of ​​each product in HPLC at different reaction times. Figure 5 It can be seen that the peak of the product appears around 6 minutes, the peak of the reactant appears around 22 minutes, and there are almost no other peaks in the middle section, indicating that the electrocatalytic reaction has high selectivity and no side reactions occur.

[0113] The catalytic reaction path, after detecting the intermediate products, 4-NP is converted into p-aminophenol (4-AP) under the conditions of the invention, and then converted into acetaminophenol (APAP). Therefore, in the whole process, 6 electrons are transferred, and 1 mol APAP can be obtained for every 1 mol 4-NP converted.

[0114] Cyclic stability test:

[0115] The CM-74 / Cu(OH) prepared in Example 1 2 The electrode was placed in an H-type electrolytic cell and used as the working electrode, the calomel electrode was used as the reference electrode, the Pt sheet was used as the counter electrode, the diaphragm was a Nafion proton exchange membrane, and a 0.1 M PBS neutral solution containing 10 mM 4-NP was used as the electrolyte. Figure 6 As shown, the horizontal axis is the number of cycles. Under the same voltage, multiple cycles show a higher APAP yield, indicating that the prepared electrode material has the characteristics of high yield and high catalytic stability for the electrocatalytic reduction of 4-NP.

[0116] CM-74 / Cu(OH) was tested in 0.1M PBS neutral solution at -0.545V vs RHE 2 The electrode material is recyclable. After 8 cycles, the catalyst can still maintain excellent 4-NP reduction conversion efficiency.

[0117] The electrocatalytic materials prepared in Example 1 and Example 2 are as follows Figure 7 shown.

[0118] The present invention realizes the preparation of transition metal-based electrode materials under mild conditions by a two-step method. First, a transition metal salt is loaded on a substrate electrode by a molten salt method, and then a transition metal-based electrode material is obtained by combining a simple hydrothermal method, and the transition metal-based electrode material is applied to the electrocatalytic reduction of nitro aromatic compounds and anhydride compounds under neutral conditions to prepare acetylamino aromatic compounds. When applied to the electro-reduction of nitro to synthesize acetylamino aromatic compounds, nitro compounds, anhydride compounds, electrocatalysts and electrolytes are placed in an aqueous solution, and aromatic nitro compounds are reduced at the cathode and acetylation reactions are coupled to prepare acetylamino aromatic compounds. Through electrocatalytic hydrogenation reaction, nitro compound reduction is achieved while combining acetylation reactions to obtain acetylamino aromatic compounds with high attachment values. The synthesis method has the characteristics of green environmental protection, simple operation, high reaction chemical selectivity, high yield, and strong universality, and the process is simple to operate, mild reaction conditions, low energy consumption, easy separation of products, and simple preparation of electrocatalyst materials, low cost, recyclable, and scalable preparation, so the invention has broad industrial application prospects in the field of industrial electrocatalytic organic synthesis and new energy.

[0119] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a transition metal electrocatalytic material, characterized in that: When the transition metal electrocatalytic material comprises a transition metal element, the preparation method comprises steps S11 and S12: S11. Immersing the conductive substrate in a system of transition metal salt and organic ligand for loading; S12. The conductive substrate loaded in step S11 is transferred to a reactor for a hydrothermal reaction. After the reaction is completed, the substrate is washed and dried to obtain a transition metal electrocatalytic material. or, When the transition metal electrocatalytic material comprises two transition metals, the preparation method comprises steps S21, S22, and S23; S21. The first transition metal salt is heated to a molten salt state and then loaded on a conductive substrate; S22. placing the substrate loaded in step S21 in an aqueous solution containing an organic ligand to react and obtain a transition metal MOFs precursor material; S23. placing the precursor material obtained in step S22 in an alkaline aqueous solution containing a second transition metal to perform a hydrothermal reaction, and after completion, washing and drying, a transition metal electrocatalytic material can be obtained on the substrate; The transition metal is selected from one or a combination of iron, cobalt, nickel and copper; The substrate comprising the transition metal electrocatalytic material is a transition metal electrocatalytic material electrode.

2. The method for preparing the transition metal heterojunction electrocatalytic material according to claim 1, characterized in that: The conductive substrate is selected from one or more of carbon paper, nickel foam, copper foam, and stainless steel mesh; In step S21, the first transition metal salt is an ionic liquid or a low-temperature molten salt; the melting point of the low-temperature molten salt is lower than 400°C; The ionic liquid is a molten salt that is in a liquid state at a temperature below 100° C., including but not limited to one or more of imidazoles, ammonium salts, and tetrafluoroborate salts of the first transition metal; In step S21, the conductive substrate is immersed in the first transition metal salt for a time of ≥5 min.

3. The method for preparing the transition metal heterojunction electrocatalytic material according to claim 1, characterized in that: The organic ligand is at least one of 2,5-dihydroxyterephthalic acid, terephthalic acid, syringic acid, gallic acid, and 1,3,5-tricarboxylic acid; The molar ratio of the transition metal to the organic ligand is 1:0.1 to 1:

10.

4. The method for preparing the transition metal heterojunction electrocatalytic material according to claim 1, characterized in that: The hydrothermal reaction step is to adjust the pH to 7-9 by using sodium hydroxide, ammonia, urea, and thiourea; The hydrothermal reaction temperature is 120-200°C, and the hydrothermal reaction time is ≥30min.

5. The transition metal heterojunction electrocatalytic material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The transition metal heterojunction electrocatalytic material is a Co-Cu heterojunction material, wherein the molar ratio of Co to Cu is 1:0.1-5; The flake or columnar components are grown on the MOF substrate to form a heterojunction with a length of micrometer level.

6. A method for electrochemically synthesizing acetylamino aromatic compounds, characterized in that: An aromatic nitro compound, an acid anhydride compound, and an aqueous electrolyte solution are used as a working electrode to construct an electrochemical reduction system, and the aromatic nitro compound is reduced at the cathode to prepare an acetylamino aromatic compound; The aromatic nitro compound is selected from nitrophenol, nitrobenzoic acid and nitrobenzene.

7. The method for electrochemically synthesizing acetylamino aromatic compounds according to claim 6, characterized in that: The acid anhydride compound is at least one of acetic anhydride, glyoxylic acid, and pyruvic anhydride; And / or, the electrochemical reduction system is a three-electrode system, further comprising a reference electrode and a counter electrode; And / or, the electrolyte solution is a neutral buffered aqueous solution, so that the pH value during the reaction is controlled at 6-8.

8. The method for electrochemically synthesizing acetylamino aromatic compounds according to claim 6, characterized in that: The electrolyte is selected from sodium (hydrogen) phosphate, potassium (hydrogen) phosphate, sodium sulfate, potassium sulfate or sodium chloride, potassium chloride, potassium (hydrogen) carbonate, sodium (hydrogen) carbonate; The electrolyte concentration is 0.01-0.1M; And / or, the electrolysis voltage is -0.2V to -0.8V, and the constant voltage reaction is ≥30min.

9. The method for electrochemically synthesizing acetylamino aromatic compounds according to claim 6, characterized in that: The concentration range of aromatic nitro compounds was 10-100 mM; The counter electrode is selected from a graphite electrode and a platinum electrode; The reference electrode is a calomel electrode.

10. Use of the method according to any one of claims 6 to 9 in the preparation of acetaminophen and acetyl-p-aminophenol.

Citation Information

Patent Citations

  • Method for synthesizing paracetamol through one-step hydrogenation

    CN113754554A